Awareness of cervical and breast cancer among women attending OBG out-patient department of a medical college hospital, Bangalore - Srikanth, Jayanthi; Upadhya, Kavya G.; Kumar, Pankaj (International Journal Of Community Medicine And Public Health, 2018)
Background: Cancers of the cervix and breast are common among Indian women. Majority of the women are not aware of the symptoms or screening methods and report late. Hence the current study was done to assess their knowledge and provide information regarding early detection. Methods: A cross-sectional study was done in the OBG out-patient department of Kempegowda Institute of Medical Science Hospital, Bangalore over a period of 3 months and 205 women aged 18 years and above were the study subjects. The awareness of the study subjects regarding cervical and breast cancer was assessed using a pre-tested semi-structured proforma. The data was analyzed using descriptive and inferential statistics. Results: Among 205 study subjects interviewed, the study subjects who had heard about cervical cancer were 173 (84.4%) and those who had heard about breast cancer were 202 (98.5%). Out of 173 subjects who had heard about cervical cancer, 139 (80.3%) had good knowledge regarding the symptoms and 102 (58.9%) knew about the risk factors. The fact that cervical cancer could be detected early was known to 113 (65.3%) subjects but only 57 (32.9%) were aware of a pap smear. Out of 202 subjects who had heard about breast cancer, 159 (78.7%) had good knowledge regarding the symptoms and 74 (36.6%) knew about the risk factors. The fact that breast cancer could be detected early was known to 143 (70.8%) subjects but only 42 (20.8%) were aware of mammogram. Conclusions: Majority of the study subjects had reasonable knowledge of the symptoms and risk factors of cervical and breast cancer but the knowledge regarding screening test for early detection of these cancers was poor.